2019
DOI: 10.9734/ijecc/2019/v9i530114
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students Willingness to Pay for Social Services of Trees at the Federal University of Agriculture Makurdi, Benue State, Nigeria

Abstract: The study was conducted to provide information on students Willingness to Pay (WTP) for social services provided by tree species on the campus of the Federal University of Agriculture Makurdi (FUAM), Benue State, Nigeria. Random sampling technique was used to select 200 students from 10 Departments of the University. The semi-structured questionnaire was used to obtain data from the students. Vegetation survey was conducted to indentified tree species present in the selected colleges. The result of the study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…People find succor or relax under trees especially during hot afternoons. These findings are consistent with other studies such as Ancha et al, [31] and Popoola and Ajewale [32].…”
Section: Discussionsupporting
confidence: 93%
“…People find succor or relax under trees especially during hot afternoons. These findings are consistent with other studies such as Ancha et al, [31] and Popoola and Ajewale [32].…”
Section: Discussionsupporting
confidence: 93%
“…Correspondingly, a questionnaire finding focused that in Nigeria out of 120 respondents, 81.67% of them preferred to include the edible insects as part of their diet. Among them, 33.2% specifically cited the insects' taste as the primary reason for their consumption (Ancha et al, 2021). In Botswana, a research by Morêki (2014) showed that approximately 53% of Mogonono villagers in Kweneng district used Carebara vidua for consumption which played an essential role in food and nutrition security.…”
Section: Records Of Consumption and Consumer Acceptance Of Edible Bla...mentioning
confidence: 99%
“…Insects are a low-cost, high-quality, and nutritious food (Tang et al, 2019). Thus, edible insects may be a viable solution for traditional entomophagous developing countries where malnutrition persists, such as Myanmar, Nigeria, and Madagascar (Ancha et al, 2021;Dürr and Ratompoarison 2021;Meysing et al, 2021).…”
Section: Global Hunger and Malnutritionmentioning
confidence: 99%